Case report: A novel JAK3 homozygous variant in a patient with severe combined immunodeficiency and persistent COVID-19 - Sbruzzi, Renan Cesar; Prado, Mayara Jorgens; Fam, Bibiana; Prolla, Helena Ashton; Hellwig, Alessandra; Motta Rodrigues, Grazielle; de-Paris, Fernanda; Jobim, Mariana; Artigalás, Osvaldo; Seeleuthner, Yoann; Casanova, Jean-Laurent; Bustamante, Jacinta; et al. (Frontiers in Immunology, 2024)
Inborn errors of immunity (IEI) encompass a broad range of disorders with heterogeneous clinical presentations, often leading to challenges in early diagnosis. This study presents a case of a Brazilian patient with a T-B+NK-severe combined immunodeficiency (SCID) diagnosed at the age of 6 months when was admitted to the hospital due to multiple infectious diseases. Despite undergoing hematopoietic stem cell transplantation (HSCT), the patient had recurrent infections, requiring constant hospital care, including IgG infusions and several antibiotic treatments for the following months. One year after HSCT, presenting mixed chimerism, the patient tested positive for SARS-CoV-2 in nasopharyngeal, duodenum, and intestine samples, with persistent positive tests over a six-month period. Whole exome sequencing identified a private homozygous missense variant (c.1202T>C; p.Leu401Pro) in the Janus Kinase 3 (JAK3) gene. This substitution is located in a highly conserved position, and different bioinformatic variant effect predictors classified the variant as damaging. In silico structural analysis suggested that the variant led to increased structural instability, disrupting the hydrophobic interactions within the SH2 domain, thereby influencing the neighboring residues and potentially altering the interaction between JAK3 and gamma chain (γc) intracellular receptors. This study provides evidence for the novel pathogenicity classification of the variant and highlights the importance of the JAK3 and SH2 domain modulating protein function and their contribution to the SCID pathogenesis.